2015
DOI: 10.1089/ars.2014.6148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Activation of the NLRP3 Inflammasome in Fibrosis: Common Threads Linking Divergent Fibrogenic Diseases

Abstract: However, studies have been conducted to suggest that modulating the calcium or the ROS axis may be of therapeutic value in regulating inflammasome activation. A number of novel drugs are currently being developed that may prove beneficial to patients suffering from fibrotic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 114 publications
0
41
0
Order By: Relevance
“…These results suggest that during Schistosoma J. infection inflammasome activation is accompanied with fibrogenic changes in the liver, which provides the first evidence that the development of SSLF may be associated with caspase-1 activation via inflammasome. In previous studies, IL-1β was found to contribute to local inflammation in response to parasitic, bacterial or viral infections [2527], and the inflammasome was reported to be involved in the complex signaling pathway driving fibrosis under different pathological conditions, and the role of inflammasomes has been related to their inflammatory or non-inflammatory effects [24]. In this regard, there are some reports that the formation and activation of NLRP3 inflammasomes in fibroblasts including HSCs may produce IL-1β or IL-18, resulting in the upregulation of transforming growth factor-β1 (TGF-β1) and collagens and also causing myofibroblast differentiation into active fibroblast to trigger or promote fibrogenesis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that during Schistosoma J. infection inflammasome activation is accompanied with fibrogenic changes in the liver, which provides the first evidence that the development of SSLF may be associated with caspase-1 activation via inflammasome. In previous studies, IL-1β was found to contribute to local inflammation in response to parasitic, bacterial or viral infections [2527], and the inflammasome was reported to be involved in the complex signaling pathway driving fibrosis under different pathological conditions, and the role of inflammasomes has been related to their inflammatory or non-inflammatory effects [24]. In this regard, there are some reports that the formation and activation of NLRP3 inflammasomes in fibroblasts including HSCs may produce IL-1β or IL-18, resulting in the upregulation of transforming growth factor-β1 (TGF-β1) and collagens and also causing myofibroblast differentiation into active fibroblast to trigger or promote fibrogenesis [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, the NLRP3 inflammasome was shown to mediate ischemia-reperfusion injury, and gene silencing of mouse Nlrp3 gene protected the liver against ischemia-reperfusion injury through reduced IL-1βand IL-18 production and decreased inflammatory cell infiltration [23]. In addition, recent studies have indicated that besides inflammation instigation and inflammatory cell infiltration the activation of NLRP3 inflammasomes in fibroblasts including HSCs may result in the upregulation of transcription factors like transforming growth factor-β1 (TGF-β1), thereby causing myofibroblast-like differentiation and proliferation [24]. Moreover, there are reports that IL-1β contributes to localized inflammation in response to parasitic, bacterial or viral infections, which may be a critical mechanism for fibrogenesis with large increases in production of extracellular matrix (ECM) such as collagens [2527].…”
Section: Introductionmentioning
confidence: 99%
“…Myofibroblasts produce collagens and other extracellular matrix proteins than underlie slowed and heterogeneous conduction in the fibrotic heart. Myofibroblasts also produce ROS, cytokines and chemokines (5), functioning as inflammatory cells. Anti-fibrotic agents and interventions may be helpful for the treatment and prevention of AF (2).…”
Section: Overview Of the Relationship Between Stress Atrial Inflammamentioning
confidence: 99%
“…Experimentally, the blockade of NLRP3 inflammasome activation or gene deletion of inflammasome molecules was shown to attenuate or abolish both inflammatory and noninflammatory effects of the NLRP3 inflammasome activation (1). Pirfenidone, as an antifibrotic drug, has been shown to inhibit NLRP3 activation and thereby decrease collagen synthesis in a model of cardiac fibrosis (2). In addition, IL-1b blockers, such as anakinra, canakinumab, and rilonacept, are now used for the clinical treatment of inflammasomemediated diseases, in particular autoinflammatory diseases.…”
Section: Targeting Nlrp3 Inflammasomes As a Therapeutic Strategy For mentioning
confidence: 99%
“…This role of inflammasome activation may not be due to its typical inflammatory response, but to its direct action on myofibroblast proliferation, differentiation, and corresponding function changes. This uncanonical action of NLRP3 inflammasome activation together with its inflammation-instigating effect is now considered as a common thread or pathological process linking divergent fibrogenic diseases (2).…”
mentioning
confidence: 99%